Time oddity: paradoxes and the gothic - Rocatelli, Vinicius Bril; Rossi, Cido (Literartes, 2021)
From the Post-structuralist perspective of the hybridity of genre-modes, this article’s goal is to explore the connection between Science Fiction and the Gothic; more specifically, from Brian Aldiss and David Wingrove’s idea, in Trillion Year Spree (1986), that Science Fiction is created by the Gothic, we tried to argue that Science Fiction can also create the Gothic. Explicitly, we argued that, through the paradoxes of narratives that work with the concept of non-linear Time Travel, Science Fiction creates Gothic effects and leads to Gothic results, once the very idea of the paradox already is inherently reactionary to the Enlightenment’s scientism and rationalism and, therefore, Gothic in its very uncanny conception.